Survey of Finger Knuckle Print Recognition and Authentication - Abdullahi, Umar; Abiola, Hambali Moshood (Darul Yasin Al Sys, 2024)
Background: Finger knuckle (FK) has gained significant attention as a biometric characteristic in recent years. Its unique features, such as visible lines, wrinkles, and ridges on the external surface of finger knuckles, make it an economically viable option for human identification. FK serves as the foundation for many biometric systems. Aim: This report presents a comprehensive analysis of relevant FK research. The typical FK identification system consists of four steps: image acquisition, image preprocessing, feature extraction, and matching. Various methods have been employed at each stage in this research. Result: The paper highlight state-of-art methods utilized for the recognition of FK.